2016
DOI: 10.25100/cm.v47i3.2457
|View full text |Cite
|
Sign up to set email alerts
|

Immunocompetence in adults: more than HIV negative

Abstract: I read a case report about Tuberculosis and fungal co-infection in a previously healthy patient published in Colomb Med (Cali) by Fontalvo et al., and I would like to address some related comments. Frequently clinicians report adult cases of patients with opportunistic infections as disseminated tuberculosis and/or fungal infections in patients consider as immunocompetent based mainly in the absence of human immunodeficiency virus infection (HIV negative). Immunocompetence is more complex than absence of HIV i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In response to the note 1 about the case described 2 , we fully agree that immunodeficiency is not only the relationship with HIV infection, and that there are pathologies and different immunological and genetic conditions associated with it 3 - 5 ; the main ones were discarded in the patient.…”
Section: Dear Editormentioning
confidence: 89%
“…In response to the note 1 about the case described 2 , we fully agree that immunodeficiency is not only the relationship with HIV infection, and that there are pathologies and different immunological and genetic conditions associated with it 3 - 5 ; the main ones were discarded in the patient.…”
Section: Dear Editormentioning
confidence: 89%
“…Thus, a total of 23 cases of culture-proven, nonrepetitive nocardiosis patients from our hospital, a 1500-bed tertiary general hospital in Beijing China, during 8-year period were characterized in our study, and we performed the Nocardia species identification by DNA sequencing and antibiotic susceptibility testing by E test method with all the available strains at the same time, instead of collecting these data retrospectively. Then these patients were divided into ISPs and ICPs groups according to the previously defined criteria, [10,11] based on their clinical characteristics. Our study showed that the 39.1% of these nocardiosis patients were ICPs and most of them recovered.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Co-infections, such as viral, bacterial, fungal pneumonia, were defined as previously described. [7] ICPs were defined following the criteria of Zea-Vera, [11] which involved not only the absence of HIV infection, but also the normal capacity to develop an immune response following the exposure to an antigen or broadly a normal immune response.…”
Section: Methodsmentioning
confidence: 99%
“…Among the most relevant causes of SID are infectious diseases (HIV, hepatitis C virus, hepatitis B virus, herpesvirus, and human T lymphotropic virus), metabolic diseases, genetic and systemic diseases (diabetes and kidney and liver diseases), malignancies (hematological and solid organ cancer), autoimmunity (systemic lupus erythematosus or amyloidosis), drugs, radiation, and others. 2,3 From my point of view, a deeper evaluation is necessary before considering as immunocompetent the patients presented in this article.…”
mentioning
confidence: 99%